KESIAPAN INTEGRASI APLIKASI SATU SEHAT DALAM MENDUKUNG REKAM MEDIS ELEKTRONIK DI RUMAH SAKIT ISLAM BANJARMASIN - Ratu Olyvia Fadillah; Muhammad Rashif Anshari; Annisa Fajarini; Nurul Noviani (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2025)
The implementation of electronic medical records must have compatibility and/or interoperability capabilities, namely the compatibility of one Electronic System with another Electronic System and the ability of different Electronic Systems to be able to work in an integrated manner to exchange data with one or more other Electronic Systems, which use data exchange standards. Based on the results of preliminary studies at Banjarmasin Islamic Hospital, preparations are currently being made to connect electronic medical records to the SATU SEHAT application. In preparation, there are several obstacles, especially in the lack of facilities and infrastructure. In addition, human resources also still need to learn the use of the Satu Sehat application, and currently there is no special officer assigned to carry it out. This study aims to determine the readiness of the SATU SEHAT application integration in supporting electronic medical records at Banjarmasin Islamic Hospital. This study used a descriptive qualitative method with observation and interview guidelines, involving 3 informants. The readiness of SATU SEHAT application integration in supporting electronic medical records at Banjarmasin Islamic Hospital has not yet reached an adequate stage.